Pengaruh Net Profit Margin, Total Assets Turnover, dan Equity Multiplier terhadap Return On Equity pada Perusahaan Food and Beverage yang Terdaftar di BEI Periode 2008 - 2010 - Pipit Yuni Wulandari; Nurdhiana Nurdhiana (Jurnal Ilmiah Aset, 2012)
This study aims to examine the effect of net profit margin (NPM), total asset turnover (TATO), and equity multiplier (EM) on return on equity (ROE) of food and beverages companies. The sample in this study were 12 food and beverages companies listed on the Indonesia Stock Exchange (BEI) from 2008-2010. Data were analyzed using multiple linear regression analysis. The results showed that only EM had a positive effect on ROE while NPM and TATO had no effect on ROE